Communicating the theory, practice and principles of language testing to test stakeholders: Some reflections. (July 2013) - Taylor, Lynda
The 33rd Language Testing Research Colloquium (LTRC), held in June 2011 in Ann Arbor, Michigan, included a conference symposium on the topic of assessment literacy . This event brought together a group of four presenters from different parts of the world, each of whom reported on their recent research in this area. Presentations were followed by a discussant slot that highlighted some thematic threads from across the papers and raised various questions for the professional language testing community to consider together. One point upon which there was general consensus during the discussion was the need for more research to be undertaken and published in this complex and challenging area. It is particularly encouraging, therefore, to see a coherent set of studies on assessment literacy brought together in this special issue of Language Testing and it will undoubtedly make an important contribution to the steadily growing body of literature on this topic, particularly as it concerns the testing of languages. This brief commentary revisits some of the themes originally raised during the LTRC 2011 symposium, considers how these have been explored or developed through the papers in this special issue and reflects on some future directions for our thinking and activity in this important area.